PENGARUH PEMBELAJARAN SIMULASI RUDAL LML LEGACY DALAM PENINGKATAN KETERAMPILAN PESERTA DIDIK DI PUSDIK ARHANUD - Bisma Adhidharma Putra Suyadi; Ahmad Nur Ahsan; Danang Kristanto Kristanto (JURNAL ELEKTROSISTA, 2026)
The author conducted a study on the influence of LML Legacy missile simulation-based learning in improving the skills of trainees at the Army Air Defense Training Center (Pusdik Arhanud). The study uses a quantitative approach through simple linear regression analysis, and data were collected through documentation within Pusdik Arhanud. The results indicate that training using a simulator system directly contributes to improved shooting skills among trainees at Pusdik Arhanud. Measures implemented included enhancements to teaching methods, regular planning and implementation of simulator training programs, direct supervision of exercises, and provision of evaluations and feedback on training outcomes. The application of shooting drill techniques strengthened trainees’ technical understanding and operational readiness. Learning strategies encompassed maintaining accuracy training records, refining instructional methods, and conducting scenario-based exercises. Structured, scenario-driven simulation combined with ongoing evaluation improved both the technical and mental readiness of personnel to face combat scenarios using modern weapon systems. The findings indicate that LML Legacy missile simulation training has a significant positive effect on improving trainees’ skills at Pusdik Arhanud. Recommendations focus on developing a simulation-based curriculum, instructor training, and integration of supporting technologies to strengthen the combat readiness of air defense personnel.